(untitled) (American Journal of Islam and Society, 1992)
Michael Marmura, the editor of this volume, has brought to his readers a valuable collection of highly respected authors, from van Ess and Frank to Anawati in part one, and from Makarem, Nasr, and Mahdi to Shehadi in part two. Each contributor to this seventeen-essay volume is an authority on his/her topic. Indeed, what we have here is a collection of essays in which by some of today ’s most competent and respected lslamicists inform the readers of the results of their scholarly research into various aspects of their discipline and thereby producing a resounding tribute worthy of a scholar of the stature of George Hourani, to whom the volume is dedicated. To be sure, not only is this work written by experts, but it is also meant for the experts. The essays are thus quite naturally extremely narrow in scope and perspective and are also self-contained and therefore independent of each other. As a result, each essay is tightly packed, and reviewing this book would mean reviewing each essay separately. Alternatively, and this would be much more desirable, the reviewer can present a general account of the problematics of Islamic theology and philosophy in which each contribution coheres to form some kind of an overall picture. But, in fairness, this is the task of the editor, not of the reviewer. Thus one wonders why Marmura, given his standing in and familiarity with the field, did not write general introductory articles for each of the volume’s two sections: "Islamic Theology" and "Islamic Philosophy." For example, it is not clear to the reader as to how and in what way van Ess’s powerful analysis of a kalam anecdote is related to Frank’s penetrating study of the kalam doctrine of bodies and atoms. For the reader, unless he/she possesses the same degree of expertise as the two authors, the only thing in common between them is that they both talk about the mutakallimun. Similarly, in more general terms, the reader legitimately wonders if there are any broad concerns, or if there are any shared methodological approaches, which bind all of those different Islamic philosophers whose thought forms the subject matter of the book’s second part. These questions could have been dealt with in an editorial panorama. Indeed, one may argue that a general account is possible only after the basic data have been collected, and since much of the classical literature of Islam still lies unstudied, a survey article would be premature. But a survey need not be definitive - it can always be tentative ...